Association of Neutrophil-Lymphocyte Ratio with Mild Cognitive Impairment in Elderly Chinese Adults: A Case-control Study - An, Peilin; Zhou, Xuan; Du, Yue; Zhao, Jiangang; Song, Aili; Liu, Huan; Ma, Fei; Huang, Guowei (Current Alzheimer research, 2019)
Inflammation plays a significant role in the pathophysiology of cognitive impairment in previous studies. Neutrophil-lymphocyte ratio (NLR) is a reliable measure of systemic inflammation. The aim of this study was to investigate the association between NLR and mild cognitive impairment (MCI), and further to explore the diagnostic potential of the inflammatory markers NLR for the diagnosis of MCI in elderly Chinese individuals. 186 MCI subjects and 153 subjects with normal cognitive function were evaluated consecutively in this study. Neutrophil (NEUT) count and Lymphocyte (LYM) count were measured in fasting blood samples. The NLR was calculated by dividing the absolute NEUT count by the absolute LYM count. Multivariable logistic regression was used to evaluate the potential association between NLR and MCI. NLR for predicting MCI was analyzed using Receiver Operating Characteristic (ROC) curve analysis. The NLR of MCI group was significantly higher than that of subjects with normal cognitive function (2.39 ± 0.55 vs. 1.94 ± 0.51, P < 0.001). Logistic regression analysis showed that higher NLR was an independent risk factor for MCI (OR: 4.549, 95% CI: 2.623-7.889, P < 0.001). ROC analysis suggested that the optimum NLR cut-off point for MCI was 2.07 with 73.66% sensitivity, 69.28% specificity, 74.48% Positive Predictive Values (PPV) and 68.36% negative predictive values (NPV). Subjects with NLR ≥ 2.07 showed higher risk relative to NLR < 2.07 (OR: 5.933, 95% CI: 3.467-10.155, P < 0.001). The elevated NLR is significantly associated with increased risk of MCI. In particular, NLR level higher than the threshold of 2.07 was significantly associated with the probability of MCI.